Pengaruh Content Marketing Tiktok Dan Konformitas Terhadap Perilaku Konsumtif Dan Keputusan Pembelian Pada Konsumen Akun Tiktok @Deliwafa - Deva Septiana Dewi; Kholid Murtadlo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this study was to determine the influence of Tiktok Content Marketing (X1) and Conformity (X2) on Consumptive Behavior (Y1) and Purchase Decisions (Y2). This study uses an explanatory research approach with quantitative methods. The collection of research data is through distributing questionnaires or questionnaires. The population in this study are consumers of the @deliwafa tiktok account. While the sample used was 100 respondents with the purposive sampling method. The data analysis technique uses SPSS version 22 software, in which the data will be processed, described and discussed to answer and prove the hypotheses proposed. The research results are as follows: (1). Tiktok Content Marketing (X1) has a positive and significant effect on consumer behavior (Y1). (2). Conformity (X2) has a positive and significant effect on consumer behavior (Y1). (3). Tiktok Content Marketing (X1) has a positive and significant effect on Purchase Decision (Y2). (4). Conformity (X2) has a negative and significant effect on Purchase Decision (Y2). (5). Consumptive behavior (Y1) has a positive and significant effect on purchasing decisions (Y2).